SISTEM INFORMASI INVENTARIS DI SDN 4 SUMBERANYAR - Ummil Mahfudoh; Zaehol Fatah (JUSTIFY : Jurnal Sistem Informasi Ibrahimy, 2023)
The inventory recording system for SDN 4 Sumberanyar school is still done manually, by recording it in an inventory book and then recapitulating it in a specialI inventory book. Then enter the inventory data into Microsoft Excel which is on the school's laptop, do not have a copy of the letter if the letter is lost because it only depends on a school laptop, and it takes a long time to search for data. With this system, it is hoped that it can provide convenience in monitoring inventory items owned by SDN 4 Sumberanyar and provide real time and accurate recapitulation of reports.